COMPREHENSIVE GEOTECHNICAL ANALYSIS OF LANDSLIDE RISK FACTORS: INSIGHTS FROM KARO REGENCY, NORTH SUMATERA, INDONESIA - Qarinur, Muhammad; Silitonga, Ernesto Maringan Ramot; Sibuea, Dody Taufik Absor; Alvan, Syahreza; Nasution, Irma Novrianty; Yacub, Mirzal (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
This study explores geological and geotechnical factors impacting landslide risk inKaro Regency, Sumatera Utara, Indonesia, a region inherently susceptible tolandslides due to its volcanic terrain. Analyzing seven landslide sites, the researchcombines field slope geometry measurements and soil bulk density tests withdetailed laboratory investigations, including Triaxial Unconsolidated Undrained(Triaxial UU) testing. Findings reveal critical insights into soil behavior, stability,and variations in shear strength parameters. The Unified Soil Classification System(USCS) identifies prevalent soil types, dominated by poorly graded sands andgravelly sands. Triaxial UU testing exposes significant variations in shear strengthparameters, highlighting soil heterogeneity. This comprehensive study contributes togeotechnical engineering, emphasizing the need for tailored mitigation strategiesand multidisciplinary approaches in effective landslide risk management in KaroRegency.